THE EFFECT OF PRICE DISCOUNT AND SERVICE QUALITY ON CONSUMER LOYALTY WITH CONSUMER SATISFACTION AS MEDIATION: (case study on consumers of the Shopee E-commerce application in Babymungil_Official stores) - Wahyu, shofif; Noni Setyorini,; Ratih Hesty Utami Puspitasari, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Economic development is currently developing rapidly, so that many new businesses compete to emerge. Based on Statista Market Insights data, the number of users of online marketplaces or e-commerce in Indonesia reached 178.94 million people in 2022. In Indonesia, there are many online marketplaces and some of them are Shopee which is familiar to the public. Shopee is ranked at the top with the most users in Indonesia. Price Discount has a significant positive influence on Consumer Loyalty. Service Quality has a significant positive influence on Consumer Loyalty. Price Discount has a significant positive influence on Consumer Satisfaction. Service Quality has a significant positive influence on Consumer Satisfaction. Consumer Satisfaction has a significant positive influence on Consumer Loyalty. Price Disocunt mediated by Consumer Satisfaction has a significant positive influence on Consumer Loyalty. Price Discount has an impact or influence on Consumer Loyalty Through Consumer Satisfaction. Service Quality mediated by Customer Satisfaction has a significant positive influence on Consumer Loyalty. The existence of Service Quality has an impact or influence on Consumer Loyalty Through Consumer Satisfaction.